Beyond the Darkness: Exploring the Myth of Solar Eclipse in The Total Solar Eclipse of Nestor Lopez and Every Soul A Star - Alvanita, Alvanita; Lutfiana, Nazra H.; Muchtarom, Aulia H. (Celt: A Journal of Culture, English Language Teaching & Literature, 2024)
Children's literature often serves as a tool for conveying complex phenomena, and one such phenomenon is the solar eclipse. While lunar eclipses have been a recurring theme in children's literature, solar eclipses have received less attention in this context. Nevertheless, in the wake of the remarkable total solar eclipse in the United States in 2017, certain children's literary works have been popular because of the use of the solar eclipse as a central theme. Noteworthy examples include The Total Solar Eclipse of Nestor Lopez by Andrea Cuevas and Every Soul A Star by Wendy Mass, both narrate tales set against the backdrop of a solar eclipse. This study examines the role played by the solar eclipse in character development and the incorporation of mythical elements within these selected novels by employing David Leeming's theory of myth, through a close reading. This study demonstrates how the solar eclipse symbolizes character growth, fostering enhanced self-confidence and self-acceptance, thereby reflecting the mythological notion that solar eclipses possess transformative potential. Furthermore, these novels encompass myths such as the act of biting during a solar eclipse, the transformation, the rituals during the eclipse, and the euphoria of the solar eclipse. However, this study also reveals instances of misinterpretation of these myths, thereby highlighting potential issues of cultural appropriation, which may contribute to children's misunderstanding.